2024
DOI: 10.1109/tvcg.2023.3285546
|View full text |Cite
|
Sign up to set email alerts
|

The Reality of the Situation: A Survey of Situated Analytics

Abstract: Hawliau Cyffredinol / General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 154 publications
0
11
0
Order By: Relevance
“…Moreover, Prouzeau et al [95] created an authoring tool for situated visualization and demonstrated the potential of involving users in tailoring visualization experiences. Two recent surveys have comprehensively summarized related works in situated visualization and analytics [78,110]. While a substantial body of research has concentrated on the visual representation and presentation of situated visualization [78], or designing interactions on mobile AR devices [110], less work focuses on interaction design [29,105].…”
Section: Designing Situatedmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, Prouzeau et al [95] created an authoring tool for situated visualization and demonstrated the potential of involving users in tailoring visualization experiences. Two recent surveys have comprehensively summarized related works in situated visualization and analytics [78,110]. While a substantial body of research has concentrated on the visual representation and presentation of situated visualization [78], or designing interactions on mobile AR devices [110], less work focuses on interaction design [29,105].…”
Section: Designing Situatedmentioning
confidence: 99%
“…Two recent surveys have comprehensively summarized related works in situated visualization and analytics [78,110]. While a substantial body of research has concentrated on the visual representation and presentation of situated visualization [78], or designing interactions on mobile AR devices [110], less work focuses on interaction design [29,105]. In addition, existing works mainly leverage the physical context of situated visualization to design interactions, without considering that users may be aware of other people when interacting with situated visualization, especially for public scenarios.…”
Section: Designing Situatedmentioning
confidence: 99%
See 3 more Smart Citations